Comparison and application of two microextractions based on syringe membrane filter. Issue 2 (4th November 2019) - Chen, Xuan; Zhang, Yanqin; Li, Zhuoyi; Bai, Xiaohong; Hu, Shuang; Wang, Runqin; Yang, Li; Zhang, Yifang; Tie, Dan
Abstract: Two proposed syringe membrane filter solid phase microextraction and syringe membrane filter liquid/solid phase microextraction, coupled separately with high performance liquid chromatography, were developed for simultaneous enrichment and determination of the trace level of flavonoids in traditional Chinese medicine. In syringe membrane filter solid phase microextraction, the membrane of syringe membrane filter was served as a solid adsorption film to adsorb target analytes. And in syringe membrane filter liquid/solid phase microextraction, the membrane of syringe membrane filter was used as not only an adsorption phase, but also as a holder of extraction solvent to realize liquid‐solid synergistic extraction. The simple operation, rapid extraction, and little or no organic solvent consumption make the two approaches very interesting. To evaluate the two proposed approaches, the crucial parameters affecting the enrichment factors of target analytes were investigated and optimized, and the two microextractions were intercompared. Moreover, their microextraction mechanisms were analyzed and described. Under the optimized conditions, both the new approaches achieved good linearities, accuracies, precisions, and low limits of detection, and the two methods were successfully applied for concentration of the flavonoids in traditional Chinese medicines.